2020
DOI: 10.1186/s12944-020-01346-z
|View full text |Cite
|
Sign up to set email alerts
|

A high fat diet with a high C18:0/C16:0 ratio induced worse metabolic and transcriptomic profiles in C57BL/6 mice

Abstract: Background: Differential effects of individual saturated fatty acids (SFAs), particularly stearic acid (C18:0), relative to the shorter-chain SFAs have drawn interest for more accurate nutritional guidelines. However, specific biologic and pathologic functions that can be assigned to particular SFAs are very limited. The present study was designed to compare changes in metabolic and transcriptomic profiles in mice caused by a high C18:0 diet and high palmitic acid (C16:0) diet. Methods: Male C57BL/6 mice were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The relative abundance of palmitate and stearate seems to be significant. Studies have demonstrated that either the genetic manipulation of the palmitate/stearate ratio in phospholipids ( 21 ) or the dietary alteration of the palmitate/stearate ratio ( 22 ) affect insulin resistance and body fat ratio. Thus, it seems likely that the palmitate/stearate ratio requires regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of palmitate and stearate seems to be significant. Studies have demonstrated that either the genetic manipulation of the palmitate/stearate ratio in phospholipids ( 21 ) or the dietary alteration of the palmitate/stearate ratio ( 22 ) affect insulin resistance and body fat ratio. Thus, it seems likely that the palmitate/stearate ratio requires regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Kang et al demonstrate that increases in visceral adipose mass, not subcutaneous adipose mass, are associated with elevated fatty acid concentrations in humans 42 . Our analysis of fatty acid profiles in dogs revealed a significant elevation in fatty acid species that have been directly implicated in the deterioration of insulin sensitivity, such as palmitic and stearic acid 43 , 44 . Furthermore, HFD feeding elevated nearly all SFA species and associated 18:1 (oleic acid) and 18:2 (linoleic acid), while significantly reducing the abundance of DPA and DHA—2 fatty acids associated with improved insulin sensitivity 45 .…”
Section: Discussionmentioning
confidence: 85%
“…Altered C18:C16 ratios and the expression of the fatty acid elongase ELOVL6 have been reported to contribute to NASH [ 28 , 43 , 44 ]. Depending on the mouse model, either elevated [ 28 ] or decreased [ 59 ] ratios have been observed, while human data indicate that reduced C18:C16 are found in steatohepatitis [ 60 ]. Interestingly, it has been shown that an age-associated upregulation of circulating C16:0 can promote pro-inflammatory monocyte polarization.…”
Section: Discussionmentioning
confidence: 99%